2010
DOI: 10.1007/s12160-010-9178-4
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial Mediators of Physical Activity and Fitness Changes in the Activity Counseling Trial

Abstract: Results indicate that behavioral interventions should incorporate methods to encourage participants to use these behavioral strategies as they attempt to become more active.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
1
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 50 publications
(84 reference statements)
3
18
1
2
Order By: Relevance
“…21 Patients received tailored counseling for each target behavior based on their current stage of change. SMI used the processes of change using the cognitive and behavioral activities found to be most effective for each stage, 22,23 and incorporated decisional balance and self-efficacy. For the decisional balance, the pros and cons of each behavior were elicited, and the counselor explored why each pro endorsed was important to the participant.…”
Section: Interventionmentioning
confidence: 99%
“…21 Patients received tailored counseling for each target behavior based on their current stage of change. SMI used the processes of change using the cognitive and behavioral activities found to be most effective for each stage, 22,23 and incorporated decisional balance and self-efficacy. For the decisional balance, the pros and cons of each behavior were elicited, and the counselor explored why each pro endorsed was important to the participant.…”
Section: Interventionmentioning
confidence: 99%
“…It appears that other variables, not measured in this study, may have caused the changes in physical activity. For example, behavioral processes of change (transtheoretical model), which have been shown to mediate change in physical activity in other studies, [15,21,33] were not assessed in this study. Although social support, self-efficacy and self-regulation were not found to be significant mediators in this study, the importance of these variables in changing older adults' physical activity should not be discounted.…”
Section: Discussionmentioning
confidence: 99%
“…Many theoretical constructs have been tested as mediators of change and results are not consistent. Self-efficacy, [10,16,20] Social support, [10] goal setting, [16,19] and behavioral processes [15,21] have been found to mediate change in physical activity behavior in some studies, although other studies have not found support for some of these constructs [12,13,16,19]. It is important to note that the samples included in these studies are quite diverse (i.e., older adults, pregnant women, cancer survivors, healthy populations).…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Porém, o conhecimento adequado do portador a respeito do papel da atividade física em sua condição de saúde influencia a incorporação da mesma em sua rotina 67,68 . Além disso, a supervisão profissional é considerada como um fator chave para o engajamento e adesão dos sujeitos 50,62,69 .…”
Section: Adesão a Programas De Atividades Físicas Para Diabéticosunclassified